Bunina bodies in motor and non‐motor neurons revisited: A pathological study of an ALS patient after long‐term survival on a respirator. Issue 4 (20th January 2014) - Kimura, Tadashi; Jiang, Haishan; Konno, Takuya; Seto, Makiko; Iwanaga, Keisuke; Tsujihata, Mitsuhiro; Satoh, Akira; Onodera, Osamu; Kakita, Akiyoshi; Takahashi, Hitoshi
<x xml:space="preserve">Abstract</x> Bunina bodies (BBs) are small eosinophilic neuronal cytoplasmic inclusions (NCIs) found in the remaining lower motor neurons (LMNs) of patients with sporadic amyotrophic lateral sclerosis (SALS), being a specific feature of the cellular pathology. We examined a case of SALS, unassociated with TDP‐43 or C9ORF72 mutation, of 12 years duration in a 75‐year‐old man, who had received artificial respiratory support for 9 years, and showed widespread multisystem degeneration with TDP‐43 pathology. Interestingly, in this patient, many NCIs reminiscent of BBs were observed in the oculomotor nucleus, medullary reticular formation and cerebellar dentate nucleus. As BBs in the cerebellar dentate nucleus have not been previously described, we performed ultrastructural and immunohistochemical studies of these NCIs to gain further insight into the nature of BBs. In each region, the ultrastructural features of these NCIs were shown to be identical to those of BBs previously described in LMNs. These three regions and the relatively well preserved sacral anterior horns (S1 and S2) and facial motor nucleus were immunostained with antibodies against cystatin C (CC) and TDP‐43. Importantly, it was revealed that BBs exhibiting immunoreactivity for CC were a feature of LMNs, but not of non‐motor neurons, and that in the cerebellar dentate nucleus, the ratio of neurons with BBs and TDP‐43 inclusions/neurons with BBs was significantly lower than in other regions. These findings suggest that the occurrence of BBs with CC immunoreactivity is intrinsically associated with the particular cellular properties of LMNs, and that the mechanism responsible for the formation of BBs is distinct from that for TDP‐43 inclusions.